Network structure and influencing factors of the quality of inbound tourism flows circulation - MA Lijun, LIANG Xiaoyao (Ziyuan Kexue)
[Objective] The objective of this study was to reveal the structural characteristics of the network of inbound tourism flows circulation quality and the role of various provinces within this network, and to analyze the influencing factors of the quality of inbound tourism flows. From a relational perspective, this study aimed to provide references for the overall enhancement of the inbound tourism flows circulation quality and the revitalization of China’s inbound tourism development. [Methods] This study extended the application of the concept of tourism flows circulation from domestic tourism to inbound tourism and explored inbound tourism flows circulation quality and its evaluation indicator system. Using inbound tourism sampling survey data from 2005 to 2019 and complex network analysis methods, this study comprehensively revealed the topological structure and evolutionary characteristics of the inbound tourism flows circulation quality network from three levels: overall, individual, and community. Finally, Quadratic Assignment Procedure (QAP) regression was used to explore the influencing factors of inbound tourism flows circulation quality. [Results] (1) The network of inbound tourism flows circulation quality exhibited small-world characteristics, but the network scale had shrunk. (2) There were significant differences in the positions and roles of different provinces within the network, and the network structure requires optimization. (3) The communities within the network of inbound tourism flows circulation quality had become clearer, and geographic agglomeration had increased. (4) The influencing factors of inbound tourism flows circulation quality such as tourism resource endowment and openness varied in their intensity and direction of impact, leading to differentiation in inbound tourism flows circulation quality. [Conclusion] The tightness of the network of inbound tourism flows circulation quality in China had decreased, and the network structure was suboptimal. Therefore, this article suggested that while China strives to expand the base of inbound tourism flows, it is also necessary to continuously promote inter-provincial tourism cooperation and expand the radius of tourism cooperation to optimize the network of inbound tourism flows circulation quality.